2010
DOI: 10.4236/jmp.2010.13029
|View full text |Cite
|
Sign up to set email alerts
|

A Cooling System with a Fan for Thermal Management of High-Power LEDs

Abstract: To improve the heat dissipation of high-power light-emitting diodes (LEDs), a cooling system with a fan is proposed. In the experiment, the LEDs array of 18 W composed of 6 LEDs of 3 W is used and the room temperature is 26ºC. Results show that the temperature of the substrate of LEDs reaches 62ºC without the fan, however, it reaches only 32ºC when the best cooling condition appears. The temperature of the LEDs decreases by 30ºC since the heat produced by LEDs is transferred rapidly by the fan. The experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Dong [8] studied on the optimization of fins parameters such as numbers, arrangement and sizes of fins for cooling of rectangular heat dissipater. Wang and Li [9] developed a heat sink for LED armature by using forced convection method with a fan at room temperature instead of natural convection. Fengze et al [10] investigated the thermal analysis of heat sinks types such as plate, in-line and staggered pin fin for cooling square LED light by using FEA.…”
Section: Introductionmentioning
confidence: 99%
“…Dong [8] studied on the optimization of fins parameters such as numbers, arrangement and sizes of fins for cooling of rectangular heat dissipater. Wang and Li [9] developed a heat sink for LED armature by using forced convection method with a fan at room temperature instead of natural convection. Fengze et al [10] investigated the thermal analysis of heat sinks types such as plate, in-line and staggered pin fin for cooling square LED light by using FEA.…”
Section: Introductionmentioning
confidence: 99%
“…Besides this, changing geometrical structure of fin or armature is a common used method to accomplish this purpose [17][18][19]. Adding a proper fan to heat sink also another effective solution to cool armature [20]. Another method to regulate the heat distribution on heat sink is the multi-LED packaging method in which higher voltage LED take places at edges and lower voltage ones at middle of armature [21].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies it is possible to reach many studies have been done by using different software in numerical modelling and CFD analysis. Main aim of these studies is to determine how much heat is dissipated by heat sink and where maximum heated regions are placed on armature and what is its effect on junction temperature [19][20][21][22][23][24][25]. Besides this, a few studies on the street type LED armature have been observed in literature and they do not include all aspects of thermal management.…”
Section: Introductionmentioning
confidence: 99%
“…LED ısı yayıcılarının etkili soğutulmasına yönelik farklı bir fikir ise Wang ve Li (2010) tarafından ortaya atılmıştır. Wang ve Li diğerlerinden farklı olarak LED ısı yayıcısının Marmara Fen Bilimleri Dergisi 2016, 2: 59-65 Led Armatürler soğutulması için fan kullanmışlardır ve yaptıkları deneysel çalışma sonucunda doğal taşınım ile 63 0 C'yi bulan bir ısı yayıcısının, fan kullanılarak 32 0 C'ye kadar soğutulduğunu saptamışlardır [8] . Ongun (2007) Gazi Üniversitesi'nde yaptığı çalışmasında, "Yol Aydınlatma Tesisatlarının Tasarımlarında Optimum Çözüm Kriterlerinin Analizi" adlı bir tez hazırlamıştır.…”
unclassified